Pregnant adolescents at risk: sexual behaviors and sexually transmitted disease prevalence. - Niccolai, Linda M; Ethier, Kathleen A; Kershaw, Trace S; Lewis, Jessica B; Ickovics, Jeannette R (American journal of obstetrics and gynecology, 2003)
The purpose of this study was to determine the level of high-risk sexual behaviors and the prevalence of chlamydia and gonorrhea among pregnant adolescents.
Keywords: Adolescent; African Americans; Chlamydia Infections; Female; Gonorrhea; Hispanic Americans; Humans; Logistic Models; Pregnancy; Pregnancy Complications, Infectious; Pregnancy in Adolescence; Pregnancy Trimester, Third; Questionnaires; Risk Factors; Sexual Behavior; Sexually Transmitted Diseases